Otitis media in coronavirus disease 2019: a case series. Issue 1 (7th January 2021) - Raad, N; Ghorbani, J; Mikaniki, N; Haseli, S; Karimi-Galougahi, M
Abstract: Background: Manifestations of the coronavirus disease 2019 in ENT include sore throat, rhinorrhoea, anosmia and dysgeusia. Whether coronavirus disease 2019 causes otitis media is not known. Objective: To assess the presence of otitis media in a series of patients with confirmed coronavirus disease 2019 and ENT symptoms. Methods: The study included patients with coronavirus disease 2019, confirmed on polymerase chain reaction assay, who had otological (e.g. otalgia, otorrhoea, hearing loss) or other ENT (e.g. anosmia, dysgeusia) manifestations of coronavirus disease 2019, in two tertiary referral hospitals in Iran. Patients were excluded if they had a background of otological problems including previous acute otitis media, chronic otitis media, otological surgery, and trauma or radiotherapy to the head and neck. Results: Otitis media was found in eight patients with coronavirus disease 2019 and no background of otological problems. Six patients had middle-ear effusion, three had typical signs of acute otitis media, and one had a tympanic membrane perforation. Most patients had hearing loss; conductive hearing loss and mild sensorineural hearing loss at high frequencies were the underlying mechanisms. Conclusion: Otitis media should be considered a manifestation or associated symptom of coronavirus disease 2019 during the current pandemic.